Living Hadith and Legal Traditions in Preserving Ancestry: A Case Study of the Contemporary Arab Sayyid Community in Lampung - Zaki, Muhammad; bin Hamid bin Syihab, Alwi; Ikhwani, Akhmad; Moh. Mukri (Faculty of Sharia, IAIN Metro, 2025)
The validity of the Arab Sayyid (Ba'alawi) lineage has been heavily debated. However, this controversy will not persist if the ulama verifies nassabah (lineage). Regardless of all that, it is certain that the Arab Sayyid community has a long history of lineage preservation. In addition to cultural factors, lineage preservation is a religious teaching with implications for family law, including marriage, guardianship, and inheritance. This article explores the practice of lineage preservation in the Arab Sayyid community in the contemporary era, revealing the normative dimensions of this practice, as expressed in a hadith, that underlie it. This research is a descriptive qualitative field research. Primary data were sourced from the Rabithah Alawiyah Management, elders, lineage observers, and members of Arab Sayyid families in Lampung. Data collection was conducted through observation, interviews, and documentation, and the data were analyzed descriptively qualitatively using the living hadith approach. The research results show that the tradition of maintaining lineage in the Arab Sayyid community in Lampung Province is maintained through introducing lineage to the family, assigning a surname, clarifying doubtful lineages, establishing sekufu' (a type of marriage), and recording lineages. This tradition embodies Sunnah values ​​because it is based on the hadith texts of the Prophet Muhammad (peace be upon him), such as the command to recognize family lineages to maintain kinship ties. This tradition represents both a cultural heritage and a living hadith that remains relevant for building the identity of the Arab Sayyid community in the contemporary era. The academic contribution of this study lies in its effort to broaden the discourse on living hadith by connecting it to the context of Islamic family law and the preservation of social identity within the Arab-descendant community. This research provides a new perspective on how hadith texts function not only as normative sources but also as living social practices that shape the legal and cultural structures of society. Moreover, this study enriches the existing literature on the integration of religious tradition and identity construction within contemporary Islamic legal studies.